Tren Penelitian Dan Jaringan Pengetahuan Kecemasan Ekologis (Ecoanxiety): Analisis Bibliometrik Menggunakan Vosviewer (2018-2024) - Fellix Rimba; Anindya Puspita Putri (PANALUNGTIK, 2025)
This study analyzes research trends and knowledge networks on eco-anxiety using a bibliometric approach with the support of VOSviewer software. Data were collected from 100 articles indexed in Google Scholar and published between 2018 and 2024. The results indicate a significant increase in publications, particularly since 2020, with a peak in 2024. Publications authored by Panu Pihkala occupy a central position with the highest citation counts, followed by studies by Stanley, Hogg, and Coffey, which expand the discourse on measurement, psychological impacts, and intervention strategies. Keyword mapping generated seven major clusters encompassing emotional dimensions (eco-guilt, eco-grief, coping), the relationship between eco-anxiety and pro-environmental actions, youth vulnerability, environmental education, and the role of social factors in shaping ecological anxiety. Temporal analysis reveals a shift in research focus from conceptualization toward intervention strategies and collective action. These findings highlight that eco-anxiety is a multidimensional issue relevant to psychology, education, mental health, and public policy, while also opening opportunities for cross-cultural research and the development of adaptive instruments to manage this phenomenon constructively